Bibliometric Analysis of Enforcement and Restitution for Victims of Human Trafficking - Rina Melati Sitompul; Elwi Danil; Mahmud Mulyadi; Mohammad Ekaputra; Rosmalinda Rosmalinda (Universitas Dharmawangsa Medan, 2025)
Human trafficking is a serious global crime, including in Indonesia, where restitution, as financial compensation for victims, plays a crucial role in their recovery and reintegration. This study uses bibliometric analysis to explore research on law enforcement and restitution in human trafficking, aiming to identify trends, key themes, and gaps. Data was gathered from the Scopus database, covering publications from 2000 to 2024. The analysis revealed a rise in human trafficking-related publications, primarily scientific articles. Seven thematic clusters were identified, focusing on law enforcement, victim protection, and sexual trafficking. However, restitution remains underexplored, with only minimal coverage in one weakly connected cluster. Bibliographic coupling and co-citation analysis highlighted key studies and journals in the field. The study concludes that restitution deserves further attention, particularly in terms of policy, challenges, and its impact on victims, to enhance protection and justice efforts.